2016
DOI: 10.1080/15376516.2016.1218577
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cytotoxicity and genotoxicity of pesticide mixtures on lymphocytes

Abstract: The cytotoxicity and genotoxicity of pesticide mixtures viz. endosulfan + chlorpyrifos, chlorpyrifos + profenofos, and endosulfan + profenofos were evaluated on cultured human peripheral blood lymphocytes using assays for cell viability, and genotoxicity using chromosomal aberrations test and comet assay. The LC values for cytotoxicity were 3.50 μM, 4.18 μM, and 10.5 μM for profenofos, endosulfan, and chlorpyrifos respectively. When combined in equimolar concentrations, the LC values for cytotoxicity were 1.4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 33 publications
(30 reference statements)
2
12
0
Order By: Relevance
“…Ability of induction of primary DNA damage was also demonstrated in human spermatozoan cells (Salazar‐Arredondo et al, ) again, at the concentrations higher than the dose tested in the present study. The third study further confirmed ability of chlorpyrifos to induce primary DNA damage and chromosome aberrations (CA) in lymphocytes isolated from healthy individuals following 2 h exposure in the range form 0,18 to 1,40 μg/mL, which corresponds to the concentrations tested in our study (Sultana Shaik et al, ). Freshwater organisms such as zebrafish (Wang et al, ), fish Channa punctatus (Bloch) (Ali et al, ) and molluscs (JanakiDevi et al, ) have been used to evaluate genotoxicity of chlorpyrifos in vivo .…”
Section: Discussionsupporting
confidence: 82%
“…Ability of induction of primary DNA damage was also demonstrated in human spermatozoan cells (Salazar‐Arredondo et al, ) again, at the concentrations higher than the dose tested in the present study. The third study further confirmed ability of chlorpyrifos to induce primary DNA damage and chromosome aberrations (CA) in lymphocytes isolated from healthy individuals following 2 h exposure in the range form 0,18 to 1,40 μg/mL, which corresponds to the concentrations tested in our study (Sultana Shaik et al, ). Freshwater organisms such as zebrafish (Wang et al, ), fish Channa punctatus (Bloch) (Ali et al, ) and molluscs (JanakiDevi et al, ) have been used to evaluate genotoxicity of chlorpyrifos in vivo .…”
Section: Discussionsupporting
confidence: 82%
“…These results suggest that the toxicity of endosulfan isomers varies with the cell type examined. Technical grade endosulfan products, or other mixtures of α and β endosulfans, have been examined extensively for cytotoxic potential [ [7] , [8] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] ]. Not surprisingly, these studies have shown that endosulfan exposure in vitro causes loss of cell viability that increases in severity as the concentration and duration of exposure increases.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, individuals would be exposed to mixtures of environmental pesticides rather than to one pesticide. In addition, low concentrations of pesticide mixtures can cause significant damage, similar to higher concentrations of individual pesticides (Sultana Shaik et al, ). Here, we found that clothianidin, acetamiprid and thiamethoxam, at the same low concentration (10μM), differently modulated ACh‐induced current amplitudes.…”
Section: Discussionmentioning
confidence: 99%